Impact of Gender Disparities on Short-Term Patient Reported Outcomes and Satisfaction Measures After Elective Lumbar Spine Surgery - Awan, Liaqat Mahmood; Talha, Muhammad; Inam, Shahzad; Shamim, Babar; Qasmi, Shahzad Ahmed; Shfiq , Waleed Bin (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the short-term patient-reported outcomes and satisfaction indicators after elective lumbar spine surgery. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Spine Surgery, Combined Military Hospital, Rawalpindi, Pakistan, from Jun to Dec 2024. Methodology: Based on gender, patients were separated into two groups. Blood loss during surgery and operating time were recorded. Prior to and following three months of surgery, patients completed patient-reported outcome measures, EuroQol 5-dimensions and the Oswestry disability index. Results: Mean age of males was 52.85±10.83 years and of females 55.41±11.75 years (p=0.308). The median (IQR) operative time was similar for both groups i.e. 193(49.0) minutes in males vs. 178(54.5) minutes in females (p=0.319). The median (IQR) blood loss was similar for both groups i.e. 262(195.5) ml in males vs. 303(170.0) ml in females (p=0.286). At baseline, the median (IQR) Oswestry disability index (ODI) score was 74(21.5) in males and 73(18.5) in females (p=0.406) but after 3 months median (IQR) ODI score was 30(10.5) in males and 34(10.0) in females (p=0.002). Median (IQR) EuroQol 5-dimensions scores at baseline were 9(1.5) in males and 9(3.0) in females (p=0.660). But after 3 months median (IQR) EuroQol 5-dimensions scores was 4(2.0) in males and 6(2.0) in females (p=0.003). The median (IQR) patient-reported outcome measures score at baseline were 14(4.50) in males and 15(5.50) in females (p=0.378). But after 3 months .... Conclusion: Outcomes of male patients were better than female patients, where surgery, seems....